Strategi Induktif Inquiry Terbimbing Guru PAI dalam Menghadapi Ketidakaktifan Peserta Didik Selama Proses Pembelajaran di SMP Negeri 2 Kota Lubuklinggau - Joko Andika; Aflia Bela Marinda; Fairus Aulia; Hendra Harmi; Mirzon Daheri (Jurnal Syntax Admiration, 2024)
Student inactivity during the learning process is one of the problems faced by Islamic Religious Education teachers which causes a decrease in student inactivity and makes the learning conditions of students uncomfortable, so the need for a guided inductive inquiry strategy carried out by Islamic Religious Education teachers to overcome student inactivity. The purpose of the study was to determine the obstacles of Islamic Religious Education teachers in dealing with student inactivity during the learning process, and to determine the efforts made by Islamic Religious Education teachers in dealing with student inactivity during the learning process. The type of research is qualitative research. Data Collection Techniques Such as Observation, Interviews, and Documentation. Data Analysis Techniques Such as Data Reduction, Data Display, and Conclusion Drawing/Verification. Data Validity Techniques Such as Observation Extension, Implementation Stage, and Data Triangulation. Based on the results of the study and discussion, it was concluded that the obstacles of Islamic Religious Education teachers were lack of preparation in teaching, lack of reflection, laziness in learning, not understanding the character of students, and lack of concentration in learning. The efforts made by Islamic Religious Education teachers are: first, teachers use a skills-based approach, second, teachers use arts-based learning methods, third, teachers use guided inquiry-based learning techniques, fourth, teachers create enjoyable learning experiences, and fifth, teachers use an experience-based approach.